An Analysis of Tourist Attractiveness of the Powiats (Districts) in the Świętokrzyskie Województwo using the PROMETHEE method - Lasek, Mirosława; Nowak, Ewa; Pęczkowski, Marek (Turyzm/Tourism, 2003)
The article presents a comparative analysis of the tourist attractiveness of powtals in the Świętokrzyskie Województwo carried out by the PROMETHEE method. It is one of the multi-criterion analytical methods based on graph theory and preference relation. The evaluation criteria were divided into eight groups: natural environment, monuments, accommodation, service infrastructure, transport accessibility, technological infrastructure, population and finances. From these eight groups 17 subcriteria were used to analyse 14 powiats. As a result the powiats were ranked according to their tourist attractiveness, and classes were established with their 'power of attractiveness’ diagnosed.